Modification of Cell Wall Polysaccharides during Drying Process Affects Texture Properties of Apple Chips - Min Xiao; Jianyong Yi; Jinfeng Bi; Yuanyuan Zhao; Jian Peng; Chunhui Hou; Jian Lyu; Mo Zhou (Journal of Food Quality)
The influences of hot air drying (AD), medium- and short-wave infrared drying (IR), instant controlled pressure drop drying (DIC), and vacuum freeze drying (FD) on cell wall polysaccharide modification were studied, and the relationship between the modifications and texture properties was analyzed. The results showed that the DIC treated apple chips exhibited the highest crispness (92) and excellent honeycomb-like structure among all the dried samples, whereas the FD dried apple chips had low crispness (10), the minimum hardness (17.4 N), and the highest volume ratio (0.76) and rehydration ratio (7.55). Remarkable decreases in the contents of total galacturonic acid and the amounts of water extractable pectin (WEP) were found in all the dried apple chips as compared with the fresh materials. The highest retention of WEP fraction (102.7 mg/g AIR) was observed in the FD dried apple chips, which may lead to a low structural rigidity and may be partially responsible for the lower hardness of the FD apple chips. In addition, the crispness of the apple chips obtained by DIC treatment, as well as AD and IR at 90°C, was higher than that of the samples obtained from the other drying processes, which might be due to the severe degradation of pectic polysaccharides, considering the results of the amounts of pectic fractions, the molar mass distribution, and concentrations of the WEP fractions. Overall, the data suggested that the modifications of pectic polysaccharides of apple chips, including the amount of the pectic fractions and their structural characteristics and the extent of degradation, significantly affect the texture of apple chips.